STRATEGI DAKWAH PEMBINA MASJID MELALUI TARBIYAH DALAM MENGATASI KENAKALAN REMAJA DI MASJID AL AMRI TOMBOLO KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This study discusses the Da'wah Strategy of Mosque Trustees through Tarbiyah in Overcoming Juvenile Delinquency at Al Amri Mosque Kuncio Kab. Gowa with the aim: To find out the da'wah strategy carried out by the mosque builder, to find out the form of delinquency before and changes in adolescents after participating in tarbiyah coaching. This type of research is qualitative research with a communication approach. The data collection was carried out by three methods: observation, interviews, and documentation, where data collection was through direct interviews with youth who took part in tarbiyah at the Al Amri mosque. The data analysis method went through three stages, namely: data reduction, understanding the data, and drawing conclusions. The results of research on teenagers who commit forms of delinquency such as gambling, wild motorbike racing, watching pornographic videos, stealing, and playing with women and do not listen to what their parents say for years. but because juvenile delinquents has forgotten a lot about how to recite the correct and appropriate tajwid. Changes in adolescents after attending tarbiyah mostly from the results of research are teenagers are aware of their actions and regret that they are far from religion and in terms of recitation many teenagers who are blind to reading in reading the Qur'an so that by frequently attending tarbiyah, teenagers have experienced changes that were previously blind to reading Now I understand Tajweed and how to read the Qur'an.